KAJIAN DINAMIKA SWELLING DARI SAMPEL-SAMPEL PLANAR MAIN-CHAIN LIQUID CRYSTAL ELASTOMER (MC-LCE) YANG DILARUTKAN DALAM KRISTAL CAIR NEMATIK - , PARMAN, Dr. Yusril Yusuf, M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Experimentally research of swelling dynamics of planar main chain liquid crystal elastomer (MC-LCE) samples has been observed, with the variation of cross-linker consentration (X) 8%, 12%, 14%, and 16% as function of time. The planar samples MC-LCE is dissolved in a cell of 5CB. The material MC-LCE will react diffusion due to the difference of chemical potential. The diffusion of 5CB causes the material expands (swollen) until it reach an equilibrium condition. The observation of swelling dynamics of planar MC-LCE samples showed the significant dimensional changes of x-axis and y-axis. The result of experiment showed the value of length expansion parameter (ð¼ð¥ð ðð¡) tend to decrease and (ð¼ð¦ð ðð¡) tend to increase by the increasing of cross-linker consentration. On swelling dynamic volume, the value of time constant tend to increace by the increasing of cross-linker consentration. Keywords : main-chain liquid crystal elastomer (MC-LCE), chemical potential, diffusion, length expansion parameter, time constant.